2022
DOI: 10.29238/sanitasi.v15i1.1226
|View full text |Cite
|
Sign up to set email alerts
|

Faktor Risiko Perilaku dan Bitting Activity Anopheles Sp. Dengan Kejadian Malaria di Indonesia: Literature Review

Abstract: Malaria is one of the vector-borne diseases that affect the morbidity and mortality of people in the world. Malaria cases recorded in 2017 were 219 million cases worldwide. In 2020, In the southeast Asian region, Indonesia was the highest contributor to confirmed malaria cases at 49.6%, followed by India at 36.4% and Myanmar at 11.5%. The purpose of this study was to determine the risk factors for people's behavior and the activity of biting Anopheles with the incidence of malaria in Indonesia. This research u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(12 reference statements)
0
0
0
Order By: Relevance
“…Mosquito repellency is a preventive effort to reduce contact between humans and mosquitoes. Residents who do not use mosquito repellents while sleeping at night are vulnerable to malaria (39). The results of this study showed that 79% of patients did not use mosquito repellents.…”
Section: The Behavior Of Malaria Sufferersmentioning
confidence: 71%
“…Mosquito repellency is a preventive effort to reduce contact between humans and mosquitoes. Residents who do not use mosquito repellents while sleeping at night are vulnerable to malaria (39). The results of this study showed that 79% of patients did not use mosquito repellents.…”
Section: The Behavior Of Malaria Sufferersmentioning
confidence: 71%